Оцінка варіацій змін швидкостей геомеханічних рухів земної кори та їх зв’язку із сейсмічними процесами в Карпатському регіоні - Ігнатишин Василь; Ihnatisin Vaszil; Ignatyshin Vasil; Ігнатишин Адальберт; Ignatyshin Adalbert; Іжак Тібор; Izsák Tibor; Izhak Tibor; Ігнатишин Моніка; Ignatyshin Monika (СумДПУ імені А. С. Макаренка, 2021)
Резюме. Розглянуто результати досліджень геодинамічного та сейсмічного стану Закарпатського внутрішнього прогину в 2019 році. Показано спектр геофізичних спостережень в регіоні, що позиціонується як сейсмогенеруючий, де протягом року сейсмічними станціями Відділу сейсмічності Карпатського регіону Інституту геофізики імені С.І. Субботіна НАН України реєструються чисельні сейсмічні події, серед яких відбуваються відчутні місцеві землетруси, що є індикатором сейсмотектонічних процесів у Карпатському регіоні. Актуальність дослідження геофізичних явищ в регіоні викликана відсутністю протягом тривалого періоду землетрусів відчутного класу, що в свою чергу підвищує ймовірність прояву сейсмічності через серію підземних відучених подій. Вивчається зв'язок просторово-часового розподілу місцевої сейсмічності у 2019 році та характеру сучасних горизонтальних рухів корив центральній частині Закарпатського внутрішнього прогину. Використовується розраховані фізичні характеристики геомеханічних рухів кори, зокрема швидкість добових зміщень верхніх шарів земної кори. Відмічено зв'язок інтервалів аномальних рухів кори із періодами сейсмічної активізації. Частота прояву місцевої сейсмічності залежить від модуля величини швидкості сучасних горизонтальних рухів: чим швидше стискаються або розширяються породи тим більша кількість землетрусів місцевого значення реєструється сейсмічними станціями.

Abstract. The study focuses on the results of studying the geodynamic and seismic state of the Transcarpathian Inner Trough in 2019. The authors show the range of geophysical observations in the region where the seismic stations of the Seismicity Department of the Carpathian region of S.I. Subbotin Institute of Geophysics of the National Academy of Sciences of Ukraine have been registering numerous seismic events for a year including perceptible local earthquakes that indicate seismotectonic processes in the Carpathian region. The topicality of researching geophysical phenomena in the region is conditioned by the absence of perceptible earthquakes for a long period of time that increases the probability of occurrence of local seismicity. The article aims at studying the spatiotemporal distribution of local seismicity, the character of modern lateral movements of the Earth's crust, analysing the relations between the region’s geodynamic state and possible ecologically hazardous processes. The object of research is seismotectonic processes in the Transcarpathian Inner Trough: modern lateral movements of the Earth's crust in the Oaș deep-seated fault area, seismic intensification of the region in 2019. The subject of research: the influence of the region’s geodynamics on the occurrence of local seismicity by using the physical parameters of geomechanic movements of the Earth's crust – the speed of daily lateral shifts of the Earth's crust in the Oaș deep-seated fault area. To reach the set aim the spatiotemporal distribution of the Carpathian region’s seismicity is studied; the kinematics of modern lateral movements of the Earth's crust has been calculated; the intervals between anomalous variations of observed geophysical fields is compared to reveal their correlation. The relation between the spatiotemporal distribution of local seismicity in 2019 and the character of modern lateral movements of the Earth's crust in the central part of the Transcarpathian Inner Trough is studied. The calculated physical characteristics of geomechanic movements of the Earth's crust are used, in particular the speed of daily shifts of the upper layers of the Earth's crust. The relation between the intervals of anomalous crustal movements and periods of seismic intensification has been observed. The frequency of occurrence of local seismicity depends on the value of speed of modern lateral movements of the Earth's crust: the quicker the rocks shorten or expand the higher the number of local earthquakes that are registered by seismic stations.
Assessing the variations of changes in the speed of geomechanic movements of the Earth's crust and their relation to seismic processes in the Carpathian region
Keywords: геодинамічний стан; сучасні горизонтальні рухи кори; сейсмічність регіону; землетруси; кінематичні параметри рухів кори; швидкість рухів; зона Оашського глибинного розлому; Закарпатський внутрішній прогин